Low voltage FLC for fast active matrix displays - Andreev, A.; Andreeva, T.; Kompanets, I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2010)
The process of FLC director reorientation in alternating electric field is considered for the case when interaction of FLC molecules with the substrates results in partial unwinding the helix structure and motion of domain walls. The hysteresis-free electrooptical response as fast as 50…70 μs was achieved in the FLC cell of 1.3-μm thickness in the electric field 1 V/μm. This result is very important for the practical use of FLC in fast active matrix displays.